OC-025 Expanded Cardia Mucosa Associated with Central Obesity Immunohistochemically Resembles Non-Im Barrett'S Mucosa. (4th June 2013) - Derakhshan, M H; Robertson, E V; Lee, Y Y; Wirz, A A; Going, J J; McColl, K E
Abstract : Introduction: Recently we showed that the length of cardiac mucosa in asymptomatic volunteers correlated with age and obesity defined by waist circumference (WC) and intra-abdominal fat on MRI (ref). To further investigate the aetiology of expanded cardia, we have performed detailed histological and immunohistological studies comparing cardia with other upper GI epithelia including long segment Barrett's with or without intestinal metaplasia. Methods: Double oriented biopsies from SCJ of the 52 H.pylori negative healthy volunteers in the original obesity study were examined. To assess inflammation, the densities of polymorphonuclear (PMN), mononuclear (MN) cell infiltrations and reactive atypia were scored at squamous, cardia and oxyntocardiac mucosae of SCJ, separately. Slides were also stained for CDX-2, Villin, TFF-3 and LI-Cadherin. The immunoreactivity in each of the three types of mucosa were compared to additional biopsies from the antrum and gastric body in same subjects and biopsies from ten patients with long-segment Barrett's demonstrating foci with and without intestinal metaplasia (IM). Results: The median scores of PMN and MN cell infiltrations were maximum in the cardia mucosa compared to either proximal or distal adjacent tissues (all p values < 0.001). The score of reactive atypia was maximum at the most distal squamous mucosa. Immunohistochemistry showed that the cardia mucosa had similarities to the antrum and Barrett's with IM; however, it was identical in all immunohistochemical aspects to non-IM Barrett's mucosa (Table). Table: The extent (%) of immunostaining with different antibodies in squamocolumnar junction, gastric body, antrum and Barrett's Conclusion: Cardia mucosa which is extended proximally in H.pylori negative healthy volunteers with central obesity, is immunohistochemically identical to non-IM Barrett's mucosa. This is consistent with the expansion of cardia mucosa having similar aetiology to Barrett's mucosa and being due to metaplasia of the most distal oesophageal mucosa resulting from short segments reflux. Disclosure of Interest: None Declared Reference: Robertson et al. Gut 2012; 61(supp 2): A256–7.